Power-shaped advanced resource assignment (PSARA) for fixed broadband wireless access systems. - Tralli, V. (IEEE Transactions on wireless communications)
We propose and investigate a new resource allocation technique for the downlink of time-division multiple access (TDMA)-based fixed broadband wireless access systems (FBWA) with full frequency reuse. This technique, named power-shaped advanced resource assignment exploits an appropriate set of power profiles which limit (or shape) the power transmitted in each slot of the frame and are suitably reused among the cells, in order to efficiently distribute the intercell and intersector interference inside the frame and to make it partially predictable. In systems where base stations assign radio resources in an uncoordinated fashion, this allows the allocation algorithm to assign time slots to users on the basis of the power required to fulfill a predefined carrier-to-interference ratio, since worst case interference can be suitably estimated; moreover, different degrees of protection against interference are provided across the slots to efficiently accommodate users with different location-dependent channel conditions. Simulation results for a typical cellular FBWA system show that this technique significantly improves the capacity with respect to other techniques recently proposed, e.g., the enhanced staggered resource assignment, even when they use power control. Moreover, an analytical framework useful to understand the concept of power shaping and to discuss some guidelines for the design of power profiles is provided.